Innovation management in crisis: patent analytics as a response to the COVID-19 pandemic - Carsten C. Guderian; Peter M. Bican; Frederik J. Riar; Sarbani Chattopadhyay (R&D Management, 2020)
Crises like the COVID-19 pandemic affect firms' innovation management and decision making. On the downside, crises lead to detriments like budget constraints, to which firms often respond by reducing their innovation activities. On the upside, crises are opportunities, where some firms exploiting changing market requirements and necessities excel. No matter in which direction, decision makers must react quickly but often rely on ad-hoc decisions or even gut feeling when drafting their crisis response strategies. Through a series of distinct cases, we demonstrate that innovation management may fill this void through patent analytics. Drawing on biochemical expertise, we particularly describe the functions and effects of COVID-19. To counter downside detriments, firms may circumvent budget constraints by discerning patents that can be (1) monetized, for example via sales or licensing deals, or (2) abandoned to achieve cost-savings, allowing firms to maintain their innovation activities. To realize upside opportunities, firms and governments may use patent analytics to detect key biotechnology firms that are likely to successfully develop treatments and vaccinations against pandemics like COVID-19. Promulgated U.S. interest in relocating foreign firms to the United States is not without technological and commercial reasoning. Herein, the insights of this study contribute to a better understanding of the use of patent information, such as smart patent indicators, harmonized patent data, novel annuity fee measures, and hand-collected datasets of COVID-19 and related antibodies' patents to the management of innovation in times of crisis.
Keywords: 650